Beyond King III: Assigning accountability for IT governance in South African enterprises - R. Butler; M. J. Butler (South African Journal of Business Management, 2010)
With the increasing dependence on IT in modern enterprises and the significant risks associated with omnipresent IT systems in business, IT governance is becoming imperative to all organisations. King III is based on the "apply or explain" approach, that forces South African entities for the first time to apply the IT governance principles as contained in the report, or explain the reasons for not applying these principles. This paper provides a macrolevel view of IT governance, derived from King III, and determined that it correlates strongly with the growing body of knowledge on IT governance. The paper investigates the responsibilities for IT governance within organisations and provides clear guidelines on the responsibilities of management roles, from the board to the operational level, involved in IT governance to ensure accountability.
Keywords: 650